2019
DOI: 10.1001/jamadermatol.2019.2941
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Analytic Modeling for Time-Effectiveness of the Sequence of Induction Treatments for Moderate to Severe Plaque Psoriasis

Abstract: IMPORTANCE Systemic psoriasis treatments vary in efficacy and cost but also in time until onset of action. Patients with no response to a first induction treatment are typically switched to another, and some patients require several treatments before they see an improvement. OBJECTIVE To determine the most cost-effective sequence of induction treatment through a comparative time-effectiveness analysis of different systemic treatment sequences currently licensed in Germany for moderate to severe plaque psoriasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 83 publications
0
8
0
1
Order By: Relevance
“…26 Sequential combination of slow acting drugs with low response rates carries a risk of long patient 'waiting times', until a noticeable, clinically meaningful improvement in their health-related quality of life. 27…”
Section: Treatment Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Sequential combination of slow acting drugs with low response rates carries a risk of long patient 'waiting times', until a noticeable, clinically meaningful improvement in their health-related quality of life. 27…”
Section: Treatment Goalsmentioning
confidence: 99%
“…Looking at the proportion of patients dropping out of clinical trials due to a lack of efficacy as a proxy, a strong increase in the rate of dropouts was seen after 10–12 weeks 26 . Sequential combination of slow acting drugs with low response rates carries a risk of long patient ‘waiting times’, until a noticeable, clinically meaningful improvement in their health‐related quality of life 27 …”
Section: Disease Severity and Treatment Goalsmentioning
confidence: 99%
“…This shows that the greatest increase in the rate of dropouts due to a lack of efficacy was seen after 10–12 weeks [10]. Sequential combination of slow acting drugs with low response rates carries a risk of long patient “waiting times”, until a noticeable, clinically meaningful improvement in their health‐related quality of life [11].…”
Section: Disease Severity and Treatment Goalsmentioning
confidence: 99%
“…[5][6][7] Similarly, a study examining the time-effectiveness of simulated induction sequences revealed that initiating treatment with ixekizumab resulted in the shortest time to achieving a clinically significant reduction in dermatology life quality index (DLQI) for 25% of patients (1Á4 weeks). 8 However, to place these findings in context, a recent update of a Cochrane NMA of overall clinical effectiveness, rather than speed of action, in achieving ≥ 90% reduction in their Psoriasis Area and Severity Index score (PASI 90) in the induction phase (8-24 weeks), established that infliximab, all the IL-17 inhibitors (ixekizumab, secukinumab, bimekixumab and brodalumab) and IL-23 inhibitors (risankizumab and guselkumab, but not tildrakizumab) were similar in efficacy. 9 In this issue of the BJD, Blauvelt et al report on the 12-week results of a novel head-to-head 24-week trial comparing ixekizumab with guselkumab (IXORA-R).…”
mentioning
confidence: 99%
“…Rapidity of clearance has been the focus of two recent network meta‐analyses (NMAs) and a systematic review, which conclude that ixekizumab and brodalumab, two agents that inhibit interleukin (IL)‐17A, are the fastest‐acting treatments when compared with other biologics and conventional systemic agents . Similarly, a study examining the time‐effectiveness of simulated induction sequences revealed that initiating treatment with ixekizumab resulted in the shortest time to achieving a clinically significant reduction in dermatology life quality index (DLQI) for 25% of patients (1·4 weeks) . However, to place these findings in context, a recent update of a Cochrane NMA of overall clinical effectiveness, rather than speed of action, in achieving ≥ 90% reduction in their Psoriasis Area and Severity Index score (PASI 90) in the induction phase (8–24 weeks), established that infliximab, all the IL‐17 inhibitors (ixekizumab, secukinumab, bimekixumab and brodalumab) and IL‐23 inhibitors (risankizumab and guselkumab, but not tildrakizumab) were similar in efficacy …”
mentioning
confidence: 99%